Equity “On the Sideline”: A Mixed Methods Study of New England Evaluation Practice in 2020 - Gates, Emily F; Williamson, Eric; Madres, Joseph; Hall, Jori N.; Benitez Alvarez, Kayla (Journal of MultiDisciplinary Evaluation, 2023)
Background: Centering equity in evaluations is increasingly recognized as an important professional responsibility of evaluators. While some theoretical and practical guidance exists, the evaluation field has limited empirical research on equity within evaluation practice. Purpose: This paper explores whether and how evaluators address inequities and advance equity throughout evaluation phases drawing on select findings from a larger study. Setting: The study focuses on American Evaluation Association-affiliated evaluators in the New England region of the United States who work in a variety of areas (e.g., health, education). Intervention: Not applicable Research Design: The study uses a complementarity, sequential mixed methods design comprised of a researcher-developed online questionnaire administered to a census and snowball sample of practicing evaluators (n=82) and individual, semi-structured interviews with a subset of this sample selected to maximize variation (n=21). Quantitative data were analyzed using descriptive statistics (i.e., means and standard deviations, frequencies). Qualitative data were analyzed using a collaborative process of deductive and inductive coding followed by thematic analysis. Findings: Eight overarching findings suggest that despite evaluators’ attempts to center equity, it remains largely “on the sideline.” This is due to evaluators’ need to work against some conventional professional and methodological norms, within contractual and contextual constraints, and with limited professional preparation.